177k views
2 votes
All you need is in the photo please don't put step by step

All you need is in the photo please don't put step by step-example-1
User Dsb
by
6.0k points

1 Answer

3 votes

A, F

1) Let's factorize x² -9x -22 =0

x² -9x -22 =0

2) Since a=1, then we can proceed this way:

Which two numbers, we can add to get -9 and multiply to get -22

3) But So we can rewrite that equation as

x² -9x -22 =0

(x -11)(x+2) = 0

4) So the answer is

(x -11)(x+2)

All you need is in the photo please don't put step by step-example-1
User Rosiane
by
5.7k points